Stable reference genes for expression studies in breast muscle of normal and white striping-affected chickens - Marciano C.M.M.* (2020)
© 2019, Springer Nature B.V.The normalization with proper reference genes is a crucial step to obtain accurate mRNA expression levels in quantitative PCR (qPCR) studies. Therefore, in this study, 10 reference candidate genes were evaluated to determine their stability in normal pectoralis major muscle of broilers and those counterparts affected with White Striping (WS) myopathy at 42 days age. Four different tools were used for ranking the most stable genes: GeNorm, NormFinder, BestKeeper and Comparative Ct (ΔCt), and a general ranking was performed using the RankAggreg tool to select the best reference genes among all tools. From the 10 genes evaluated in the breast muscle of broilers, 8 were amplified. Most of the algorithms/tools indicated the same two genes, RPL30 and RPL5, as the most stable in the broilers breast muscle. In addition, there was agreement among the tools for the least stable genes: MRPS27, GAPDH and RPLP1 in the broilers breast muscle. Therefore, it is interesting to note that even with different tools for evaluating gene expression, there was consensus on the most and least stable genes. These results indicate that the Ribosomal protein L30 (RPL30) and Ribosomal protein L5 (RPL5) can be recommended for accurate normalization in qPCR studies with chicken pectoralis major muscle affected with White Striping and other myopathies.